The performance and analysis of the thermoelectric generator system used in diesel engines - Temizer, Ilker; Ilkilic, Cumali (Pergamon-Elsevier Science Ltd, 2016)
Thermoelectric generator (TEG) has drawn significant for the waste heat recovery systems. In this study, a prototype has been developed for the working principle suitable to the thermoelectric generator systems. The exhaust system of diesel engine is used and benefited from the exhaust gas heat to heat the surface. In addition, thermoelectric cooling system is used for the cooling effect that is required under different temperatures. In experiments, internal combustion diesel engines are used in five different engine speeds and two different engine loads for each speed level. Electric connection of the 40-piece thermoelectric modules mounted on the octagon structure made from Aluminium 6061 material is made in series. Performance of TEG systems has been examined in terms of changing speed and engine load. The performance of TEG systems has been examined in terms of changing speed and load in the engine. In the system, with the assistance of fluent programme in the Ansys Workbench 12.0 and at the same time having the Calculating Fluid Dynamic (CFD) programme, the temperature and flow analysis is performed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Waste heat recovery; Thermoelectric generation; Calculated fluid dynamic